2012
DOI: 10.1051/0004-6361/201219001
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric mapping of the 3.3-mm continuum emission of comet 17P/Holmes after its 2007 outburst

Abstract: Context. Comet 17P/Holmes underwent a dramatic outburst in October 2007, caused by the sudden fragmentation of its nucleus and the production of a large quantity of grains scattering sunlight. Aims. We report on 90 GHz continuum observations carried out with the IRAM Plateau de Bure interferometer on 27.1 and 28.2 October 2007 UT, i.e., 4−5 days after the outburst. These observations probed the thermal radiation of large dust particles, and therefore provide the best constraints on the mass in the ejecta debri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 28 publications
6
29
0
Order By: Relevance
“…It is found that the infrared spectrum of the diffuse emission can be explained by a mixture of amorphous and crystalline silicate materials as observed in most comets (Watanabe et al 2009;Reach et al 2010). Total ejecta mass was estimated to be 10 10 -10 13 kg (Montalto et al 2008;Altenhoff et al 2009;Reach et al 2010;Ishiguro et al 2010;Boissier et al 2012). More than a 2-m-thick surface layer could be blown off by the initial event although this is strongly dependent on the size distribution and maximum size of the dust par-ticles .…”
Section: P/holmes Is a Distinguished Comet Because Of Its Spectaculmentioning
confidence: 96%
“…It is found that the infrared spectrum of the diffuse emission can be explained by a mixture of amorphous and crystalline silicate materials as observed in most comets (Watanabe et al 2009;Reach et al 2010). Total ejecta mass was estimated to be 10 10 -10 13 kg (Montalto et al 2008;Altenhoff et al 2009;Reach et al 2010;Ishiguro et al 2010;Boissier et al 2012). More than a 2-m-thick surface layer could be blown off by the initial event although this is strongly dependent on the size distribution and maximum size of the dust par-ticles .…”
Section: P/holmes Is a Distinguished Comet Because Of Its Spectaculmentioning
confidence: 96%
“…Epifani et al (2001) showed millimeter-sized dust in the coma of 2P/Encke typically had velocities of <10 m s −1 but reached velocities >30 m s −1 approximately two weeks before perihelion. On the other hand, Boissier et al (2012) found a population of millimeter-sized grains in the coma of 17P/ Holmes with velocities of 50-100 m s −1 after a fragmentation event. Sekanina & Chodas (2012) determined that as C/2013 W3 (Lovejoy) was disrupted shortly after perihelion, the millimeter-sized dust was released at velocities of up to 30 m s −1 .…”
Section: Dust Mass and Mass-loss Ratementioning
confidence: 94%
“…Boissier et al 2012). Though sample opacities for millimeter-sized grains of varying porosity, ice/silicate mixture, and size distribution have been published (Jewitt & Luu 1990;Boissier et al 2012), the nature of the millimeter grains cannot be determined with these observations. Dust masses could be significantly higher if the millimeter-sized dust grains are very porous, containing little ice.…”
Section: Dust Mass and Mass-loss Ratementioning
confidence: 99%
See 1 more Smart Citation
“…We used the model of dust thermal emission presented by Boissier et al (2012). Absorption cross-sections were calculated with the Mie theory, taking a refractive index ((n, k) = (2.05, 0.007) at 1.91 mm) corresponding to porous grains (P = 0.5) composed of a 50:50 mixture of crystalline (Fabian et al 2001) and amorphous silicates (Draine 1985).…”
Section: Dust Contributionmentioning
confidence: 99%